WRITING WORKSHOP OF SCIENTIFIC ARTICLES FOR SENIOR HIGH SCHOOL TEACHERS - Endang Purwaningsih; Yessi Affriyenni; Sentot Kusairi; Sutopo Sutopo (JCES (Journal of Character Education Society), 2021)
Abstrak: Harapan akan meningkatnya kualitas pendidikan di Indonesia mulai terwujud sejak diberlakukannya program sertifikasi guru oleh pemerintah sebagai upaya peningkatan kualitas dan kesejahteraan guru di Indonesia. Pemberlakuan kuota dan prioritas bagi guru yang telah memenuhi syarat minimal kualifikasi akademik dan masa kerja serta panjangnya antrian proses sertifikasi membuka kesempatan bagi guru-guru untuk mempersiapkan diri lebih dalam mengikuti sertifikasi guru dalam jabatan dengan matang. Salah satu komponen portofolio yang harus disiapkan adalah karya pengembangan profesi dimana guru dituntut untuk menghasilkan karya tulis ilmiah. Untuk itu, workshop ini bertujuan untuk membantu guru melalui pendampingan penyusunan artikel ilmiah dan publikasinya. Kegiatan pengabdian masyarakat ini tersusun dalam tiga kegiatan yakni persiapan, pelaksanaan, dan evaluasi. Dalam pelaksanaannya, kegiatan terdiri atas workshop sebanyak enam pertemuan, diskusi dan konsultasi secara daring, serta klinik penyempurnaan naskah artikel. Kegiatan dilaksanakan di SMA Laboratorium Universitas Negeri Malang. Hasil luaran dari kegiatan ini adalah artikel ilmiah guru yang telah dikirimkan ke seminar maupun jurnal berskala nasional atau internasional.Abstract:  The expectation on the improvement of education quality in Indonesia has started to be realized since the enactment of the Teacher Certification Program (TCP) by the government as an effort to improve teachers’ quality and prosperity in Indonesia. The implementation of quota and priority limitations for teachers who have met the minimum requirement either academically or based on years of service along with the long period of queue time for the certification process has opened the opportunity for the teachers to prepare themselves more carefully. One of the portfolio components that need to be prepared is the professional development papers where teachers are expected to write scientific papers. Hence, this workshop aims to help teachers through the writing assistance of scientific articles and publications. This community service consisted of three main activities including the preparation, the execution, and the evaluation. In the execution stage, the activities include six offline workshops, online discussion and consultation, and the clinic of article draft finishing. This workshop was held in Universitas Negeri Malang (UM) Laboratory Senior High School. Result outcome from this workshop is teachers’ scientific articles published either through national or international scale conferences or journals.